Video 1987 St Patricks Day - Walsh, Leo Mackey, Paddy Murphy, Rob Creagh, Seamus Walsh, Don Russell, Kelly, 1956- Barron, Vonnie Walsh, Monica Keenan, Una (1987)
Clip from some Irish TV documentary on Paddy's Day. Leo Walsh is interviewed. The band is Paddy Mackey, Rob Murphy, Seamus Creagh, Don Walsh and Kelly Russell. Also in the room are Vonnie Barron, Monica Walsh and I believe Una Keenan.